2022
DOI: 10.1111/cch.13009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental referrals of pre‐school children in a diverse community in England: The importance of parental migration for referral rates

Abstract: Background Children born to migrant parents have higher rates of language difficulties, intellectual disability and autism. This study explores the relationship between migration, ethnicity and reasons for early years referrals to community paediatrics in a diverse multi‐cultural population in a city in south west England. Methods Observational retrospective study from a community paediatric service serving a multi‐cultural urban population from June 2012 to February 2016. We tested associations of ethnicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies in Southeast Asia have identified factors associated with parenting stress in parents of children with autism, such as social support and financial difficulties (Ilias et al, 2018). Additionally, research has shown that parental migration can influence the risk of autism in children, with first-generation immigrant parents having a higher incidence of autism spectrum disorders (Allport et al, 2022).…”
Section: Related Studies On Parents Of Children With Autismmentioning
confidence: 99%
“…Studies in Southeast Asia have identified factors associated with parenting stress in parents of children with autism, such as social support and financial difficulties (Ilias et al, 2018). Additionally, research has shown that parental migration can influence the risk of autism in children, with first-generation immigrant parents having a higher incidence of autism spectrum disorders (Allport et al, 2022).…”
Section: Related Studies On Parents Of Children With Autismmentioning
confidence: 99%
“…It is also considered a Western disease that only affects Somali children in the diaspora [ 19 ]. Similarly, a study in the UK reported that children of Somali descent are six-times (RR 5.99, 95% CI 3.24–10.8, p < 0.001) more likely to be referred for possible autism spectrum than their white or mixed-race peers [ 24 ]. So far, studies did not investigate or even postulate reasons for overrepresentation of Somali children in the USA or Europe for ASD.…”
Section: Introductionmentioning
confidence: 99%